2010
DOI: 10.1007/s00330-010-2009-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in patients with nipple discharge: should we recommend it?

Abstract: In women with ND, CEMRI should be recommended when conventional imaging is negative. Unexplained ND could be considered an indication for CEMRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 22 publications
7
69
1
1
Order By: Relevance
“…However, further studies are required to define its role more clearly, as there are still limitations in clinical practice (8)(9)(10)(11)(12)(13)(14). Magnetic resonance imaging (MRI) may play an adjunctive role, aiding in the differentiation of benign ductal abnormalities from malignant ones (15)(16)(17)(18). Although not a routine practice in the United Kingdom; a number of techniques have been used to determine the cause of nipple discharge, beyond the triple assessment.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are required to define its role more clearly, as there are still limitations in clinical practice (8)(9)(10)(11)(12)(13)(14). Magnetic resonance imaging (MRI) may play an adjunctive role, aiding in the differentiation of benign ductal abnormalities from malignant ones (15)(16)(17)(18). Although not a routine practice in the United Kingdom; a number of techniques have been used to determine the cause of nipple discharge, beyond the triple assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Lorenzon et al (2011) found that CEMRI could identify 5/5 cancers (sensitivity = 100%) and 13/14 high-risk lesions (sensitivity = 92.9%) (overall sensitivity, 94.7%; overall specificity, 78.9%). In addition, it was found that 3 of 5 cancers (1 invasive, 1 in situ, 1 contralateral invasive) and 2 of 14 highrisk lesions could be detected only by CEMRI.…”
Section: Localization Of the Disease Causing The Ndmentioning
confidence: 96%
“…DG is invasive and time-consuming with potential complications including intense pain, mastitis, lymphatic opacification, and duct perforation (Cardenosa et al, 1994;Lorenzon et al, 2011;Tabar et al, 1983). The rate of incomplete and/or technically inadequate conventional DG has been reported to be as high as 10-15% (Morrogh et al, 2008;Sickles, 2000).…”
Section: Ductography (Dg Also Called Galactography)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is the third most common breast complain after breast pain and breast lump, with a reported prevalence of 4.8-7.4%. 2 It is a true, direct drainage from the mammary duct or ducts, which appears on the surface of the nipple.…”
Section: Introductionmentioning
confidence: 99%